Penerapan Teknologi Biogas sebagai Sumber Bahan Bakar dan Pupuk Organik untuk Meningkatkan Kesejahteraan Petani di Desa Pinaling Minahasa Selatan - Jeanne Paulus; Lady Corrie Chantique Emma Lengkey; Jemmy Najoan (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The Farmers Group "Bekerja Bersama" as a partner group is one of the farmer groups in Pinaling village, East Amurang sub-district, South Minahasa district. Based on the survey results, farmer groups have low economic conditions and crop productivity. The Community Partnership Program (PKM) with the application of biogas technology aims to: 1) Utilize organic waste to produce biogas as a substitute for LPG through biogas technology, 2) Utilize liquid organic fertilizer (POC) as a by-product of biogas technology to increase crop production; and 3) Increase crop production and improve farmers' welfare. PKM activities are carried out in Pinaling Village, East Amurang Sub-district, South Minahasa District in May‒August 2021. The implementation methods include counseling, training, demonstration plots, and evaluation. Through this program, the following achievements were obtained: 1) The application of biogas technology can produce biogas as a substitute for LPG, thereby saving the cost of LPG fuel by 30% from the price of Rp. 138,000/18 kg/month to Rp. 46,000/month; 2) The application of technology biogas can produce liquid organic fertilizer, so it can save costs on the purchase of chemical fertilizers by 50% from Rp. 1,750,000/ha/planting season to Rp. 875,000/planting season; and 3) The application of biogas technology can increase the production of lowland rice by 62.5% compared to the previous planting season (before using POC) to increase farmers, income and welfare.